A lithium ion battery electrolyte and a preparation method thereof

CN119381571BActive Publication Date: 2025-03-07ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411943166.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-07
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The film-forming additives in the existing lithium-ion battery electrolyte have large film-forming impedance, poor power performance and poor high temperature stability, making it difficult to achieve both high-voltage performance and power performance, resulting in poor circulation performance of lithium-ion batteries.

Method used

Two-component additives (additive 1 and additive 2) are added to the lithium-ion battery electrolyte. The additive 1 suppresses the acidity by eliminating trace amounts of water and hydrofluoric acid in the electrolyte. The additive 2 reduces the degree of solvation of Li+ and reduces side reactions, and builds an interface layer rich in inorganic components to improve interface stability and the flux of Li+ migration channels.

Benefits of technology

通过双组分添加剂的协同作用,显著改善了锂离子电池的整体性能,提高了电池的循环稳定性和容量保持率,增强了正极材料的抗裂性,兼顾了高压性能和功率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381571B_ABST
    Figure CN119381571B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and in particular, relates to a lithium-ion battery electrolyte and a preparation method thereof. The synergistic effect of the two-component additives TTP and NST of the present invention significantly improves the microstructure and macroscopic electrochemical performance of the NCM811 electrode, and improves the cycle stability and capacity retention rate of the battery. The role of the two-component additive in the electrolyte is to construct a positive electrode-electrolyte interface layer and a negative electrode-electrolyte interface layer of LiF and Li3N by optimizing the chemical reaction on the electrode surface and the formation of the interface layer, thereby effectively inhibiting the decomposition of the electrolyte and the non-uniform deposition of lithium. The electrode-electrolyte interface layer regulated by the combination of the LiF and Li3N components has both high mechanical strength and high-flux Li + The migration channel is beneficial to protect the electrode material from the erosion of the electrolyte while promoting rapid and uniform Li deposition, enhancing the crack resistance of the positive electrode 811 material, thereby enhancing the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery electrolyte and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been successfully used in 3C digital electronic products, electric vehicles and other fields. 2 ), nickel-rich layered oxide cathode materials have become the mainstream choice for post-lithium-ion batteries (LIBs) due to their relatively low cost and high reversible capacity. At the same time, increasing the operating voltage of the battery can further increase the energy density of the battery. However, the cycle life and safety of this battery system have severely limited its further promotion and use, mainly because the nickel-rich cathode in the commercial lithium hexafluorophosphate (LiPF 6 )There are serious interfacial stability challenges in carbonate-based electrolyte systems.

[0003] First, the performance of lithium-ion batteries decreases with the increase of positive electrode nickel content. This is because the increase of positive electrode nickel content leads to an increase in the oxidation number of nickel, and high-valent nickel atoms tend to be reduced to a lower oxidation state, resulting in oxygen evolution and structural degradation of positive electrode active materials. At the same time, high-valent nickel atoms will cause severe electrolyte decomposition, further leading to high impedance cathode electrolyte interface (CEI) and poor Li + Secondly, corrosive acidic compounds such as HF (formed by LiPF 6 Hydrolysis) will corrode the positive electrode material, thereby dissolving Ni 2+ This leads to the degradation of the positive and negative electrode materials, increases the crosstalk effect between batteries, and accelerates the battery cycle life decline. 2+ Reduction at the negative electrode (such as graphite) destroys the solid electrolyte interface (SEI), further catalyzes the reduction of the electrolyte, and hinders the Li + Embedded in the negative electrode. These side reactions are more severe under high voltage and high temperature conditions. In order to better exert the performance of high-nickel positive electrodes, the regulation of electrolyte composition and structure is undoubtedly a simple and efficient modification method, which plays a decisive role in the electrochemical stability of the electrolyte body and the electrode-electrolyte interface.

[0004] At present, in order to extend the service life of batteries and alleviate the side reactions that occur during long battery cycles, a variety of strategies have been developed. 2 O 3 , LiAlO 2The reaction probability of active materials and electrolyte under high pressure can be reduced, but the anisotropic phase change produced during the lithium insertion and extraction process will cause separation between the positive electrode particles and the coating layer. At the same time, the coating layer is mostly a poor conductor of lithium ions. When the coating layer is too thick, it will affect the Li + Diffusion, inhibition of Li + Intercalation and deintercalation at the interface of cathode materials.

[0005] From the perspective of electrolyte, there are mainly the following ways: for example, constructing a high-concentration / locally high-concentration electrolyte system, developing new electrolyte solvents / lithium salts, artificially constructing a strong interface layer, and developing functional electrolyte additives. Among them, adding additives to the electrolyte is both economical and effective. Adding electrolyte additives can obtain in-situ generated CEI and improve the coulombic efficiency and cycle stability of high-nickel ternary positive electrode materials. The properties of the electrolyte affect the interface stability, thermodynamic stability and Li + Transfer kinetics at the electrode / electrolyte interface. Trace amounts of electrolyte additives can affect LiPF 6 The decomposition process of the nickel-rich cathode is reduced, the decomposition of salt is reduced, and sacrificial additives are selected to form a film first, effectively isolating the high catalytic activity cathode and the electrolyte, reducing the reaction between the residual alkali on the surface of the high nickel cathode and the HF in the electrolyte, and the decomposition of carbonate solvents, thereby reducing the possibility of battery bloating. Additives can also effectively remove H 2 O, HF or coordinate with the lattice oxygen of the positive electrode to increase the lattice oxygen deintercalation barrier and inhibit the release of active oxygen. At present, most film-forming additives have relatively single functions. For example, the commonly used negative electrode film-forming additive vinyl carbonate can effectively improve the high-temperature cycle stability of the battery, but its film-forming impedance is large and it cannot take into account the power performance; while the SEI film formed by fluoroethylene carbonate has low impedance and good power performance, but its high-temperature stability is insufficient and gas production is serious. In order to meet the requirements of high energy density and long cycle life for batteries, multiple additives are usually used in combination, which often cannot achieve a balance between high voltage performance and power performance. Summary of the invention

[0006] The present invention aims to overcome the defects of the film-forming additives in the lithium-ion battery electrolyte in the prior art, such as large film-forming impedance, poor power performance, poor high-temperature stability, severe inflation, difficulty in achieving both high-voltage performance and power performance, resulting in poor cycle performance of the lithium-ion battery. A lithium-ion battery electrolyte and a preparation method thereof are provided to overcome the above defects.

[0007] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0008] A lithium ion battery electrolyte comprises a lithium salt, an organic solvent, an additive 1 and an additive 2, wherein the structural formula of the additive 1 is shown in formula (1), and the structural formula of the additive 2 is shown in formula (2):

[0009]

[0010] Among them, R 1 ~R 8 Each of the following is independently selected from a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyleneoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted alkenyleneoxy group having 2 to 10 carbon atoms, a substituted or unsubstituted epoxyalkylene group having 2 to 10 carbon atoms, a substituted or unsubstituted boroxyalkylene group having 1 to 10 carbon atoms, and a substituted or unsubstituted arylene group having 6 to 10 carbon atoms.

[0011] The present invention adds a two-component additive (additive 1 and additive 2) to the lithium-ion battery electrolyte. The additive molecules will regulate the interface components and synergize with the electrolyte solvation, which helps to enhance the overall performance of the lithium-ion battery. During the battery charging and discharging process, the additive molecules added to the positive electrode material will first form a film on the positive electrode surface to construct an interface layer. At the same time, the additive molecules in the solution will undergo redox reactions before the organic solvent. Based on the fluorine-containing and amino functional groups rich in the additives, it can promote the generation of inorganic components rich in LiF and Li 3 N positive electrode-electrolyte interface layer and negative electrode-electrolyte interface layer. 3 The electrode-electrolyte interface layer regulated by N component combination has both high mechanical strength and high flux Li + Migration channels are beneficial for protecting electrode materials from electrolyte corrosion while promoting rapid and uniform Li + Deposition further enhances the crack resistance of the positive electrode material.

[0012] In addition, the different additive molecules added to the lithium-ion battery electrolyte of the present invention exert different effects due to the different functional groups they carry. The additive 1 molecule can effectively eliminate trace water and hydrofluoric acid in the electrolyte due to its characteristic functional groups of trifluoroacetate and trimethylsilyl, thereby inhibiting the acidity of the lithium-ion battery electrolyte and further reducing the corrosion of the lithium-ion battery electrolyte on the electrode material. The additive 2 molecule can enter the lithium-ion battery electrolyte due to its unique amide structure. + The first solvation sheath layer of the lithium ion battery electrolyte reduces the Li + At the electrode-electrolyte interface during battery charge and discharge, this reduced Li + The solvated structure can effectively reduce the side reactions of decomposition of free solvent molecules, further improve the oxygen resistance of the electrolyte, and promote the construction of a strong and uniform inorganic molecular interface layer.

[0013] Preferably, the lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium difluorooxalatoborate, lithium hexafluoroarsenate and lithium difluorophosphate.

[0014] Preferably, the organic solvent is any one or more combinations of cyclic carbonate, chain carbonate, and carboxylate co-solvents.

[0015] Preferably, the organic solvent is any one or more of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate.

[0016] The method for preparing a lithium ion battery electrolyte as described above comprises the following steps:

[0017] In a glove box, a lithium salt is added to an organic solvent under stirring and completely dissolved to obtain a blank electrolyte; then, additive 1 is added to the blank electrolyte, and after it is fully dissolved, additive 2 is added thereto to obtain a lithium-ion battery electrolyte.

[0018] Preferably, the concentration of the blank electrolyte is 0.8-1.2 mol / L.

[0019] As further preferred, the concentration of the blank electrolyte is 1 mol / L.

[0020] Preferably, the weight percentage content of the additive 1 contained in the lithium-ion battery electrolyte is 0.2-3wt%.

[0021] As a further preference, the weight percentage content of the additive 1 contained in the lithium-ion battery electrolyte is 1 wt %.

[0022] Preferably, the weight percentage content of the additive 2 contained in the lithium-ion battery electrolyte is 0.2-3wt%.

[0023] As a further preference, the weight percentage content of the additive 2 contained in the lithium-ion battery electrolyte is 1 wt %.

[0024] Preferably, the weight percentage content of lithium salt contained in the blank electrolyte is 1-2wt%.

[0025] As a further preference, the weight percentage content of lithium salt contained in the blank electrolyte is 1.5wt%.

[0026] Preferably, the organic solvent comprises cyclic carbonate and chain carbonate, the cyclic carbonate accounts for 20-30% of the total mass of the organic solvent, and the chain carbonate accounts for 70-80% of the total mass of the organic solvent.

[0027] As further preferred, the organic solvent comprises cyclic carbonate and chain carbonate, the cyclic carbonate accounts for 30% of the total mass of the organic solvent, and the chain carbonate accounts for 70% of the total mass of the organic solvent.

[0028] Therefore, the present invention has the following beneficial effects:

[0029] (1) The present invention adds a two-component additive (additive 1 and additive 2) to the lithium-ion battery electrolyte. The additive molecules regulate the interface components and synergize with the electrolyte solvation, thereby helping to enhance the overall performance of the lithium-ion battery.

[0030] (2) During the battery charging and discharging process, the additive molecules added to the positive electrode material will first form a film on the positive electrode surface to construct an interface layer. At the same time, the additive molecules in the solution will undergo redox reactions before the organic solvent. Based on the fluorine-containing and amino functional groups rich in the additives, the inorganic components LiF and Li 3 N positive electrode-electrolyte interface layer and negative electrode-electrolyte interface layer. 3 The electrode-electrolyte interface layer regulated by N component combination has both high mechanical strength and high flux Li + Migration channels are beneficial for protecting electrode materials from electrolyte corrosion while promoting rapid and uniform Li + Deposition, further enhancing the crack resistance of the positive electrode material;

[0031] (3) The additive 1 molecule of the present invention can effectively eliminate trace water and hydrofluoric acid in the electrolyte due to its characteristic functional groups, trifluoroacetate and trimethylsilyl, thereby inhibiting the acidity of the lithium-ion battery electrolyte and further reducing the corrosion of the lithium-ion battery electrolyte on the electrode material. The additive 2 molecule can enter the lithium-ion battery electrolyte due to its unique amide structure. + The first solvation sheath layer of the lithium ion battery electrolyte reduces the Li + The degree of solvation;

[0032] (4) At the electrode-electrolyte interface during battery charge and discharge, this reduced Li + The solvated structure can effectively reduce the side reactions of decomposition of free solvent molecules, further improve the oxygen resistance of the electrolyte, and promote the construction of a strong and uniform inorganic molecular interface layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Figure a shows the surface morphology of the positive electrode 811 material after long-term cycling in a blank electrolyte;

[0034] Figure 1Figure b is a surface morphology of the positive electrode 811 material after long-term circulation in the lithium-ion battery electrolyte in Example 1;

[0035] Figure 1 Figure c shows the internal morphology of the positive electrode 811 material after long-term cycling in a blank electrolyte;

[0036] Figure 1 Figure d is a diagram showing the internal morphology of the positive electrode 811 material after long-term cycling in the lithium-ion battery electrolyte in Example 1.

[0037] Figure 2 This is a comparison of the capacity retention rates of graphite / NCM811 full batteries using different electrolytes under 1C 2.8-4.7V and 200 cycles. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a lithium ion battery electrolyte and a preparation method thereof.

[0041] A lithium-ion battery electrolyte comprising lithium hexafluorophosphate (LiPF 6 ), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), additive 1 (TTP) and additive 2 (NST), the structural formula of the additive 1 (TTP) is shown in formula (3), and the structural formula of the additive 2 (NST) is shown in formula (4):

[0042]

[0043] A method for preparing the lithium ion battery electrolyte as described above comprises the following steps:

[0044] In a glove box, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a mass ratio of 1:1:1 (EC accounted for 30% of the total mass of the organic solvent, and EMC and DMC accounted for 70% of the total mass of the organic solvent). Lithium hexafluorophosphate (LiPF 6) and dissolve it completely to obtain a blank electrolyte with a concentration of 1 mol / L (wherein the weight percentage of lithium salt contained in the blank electrolyte is 1.5 wt%). Then, additive 1 (TTP, with the structural formula shown in formula (3)) is added to the blank electrolyte. After it is fully dissolved, additive 2 (NST, with the structural formula shown in formula (4)) is added thereto to obtain a lithium-ion battery electrolyte. Wherein, the weight percentage of additive 1 (TTP) contained in the lithium-ion battery electrolyte is 1 wt%, and the weight percentage of additive 2 (NST) contained therein is 1 wt%.

[0045] As another embodiment, when preparing a lithium-ion battery, the additive 1 (TTP) may be added to the slurry of the positive electrode material.

[0046] Example 2

[0047] This embodiment provides a lithium ion battery electrolyte and a preparation method thereof.

[0048] The difference between this embodiment and embodiment 1 is that:

[0049] A method for preparing a lithium ion battery electrolyte, wherein ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are uniformly mixed at a mass ratio of 8:15:15 (wherein EC accounts for 20% of the total mass of the organic solvent, and EMC and DMC account for 75% of the total mass of the organic solvent); a blank electrolyte with a concentration of 0.8 mol / L is obtained (wherein the weight percentage content of lithium salt contained in the blank electrolyte is 1 wt%); the weight percentage content of additive 1 (TTP) contained in the lithium ion battery electrolyte is 0.2 wt%, and the weight percentage content of additive 2 (NST) contained is 3 wt%. Others are the same as in Example 1.

[0050] Example 3

[0051] This embodiment provides a lithium ion battery electrolyte and a preparation method thereof.

[0052] The difference between this embodiment and embodiment 1 is that:

[0053] A method for preparing a lithium ion battery electrolyte, wherein ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are uniformly mixed in a mass ratio of 2:3:3 (wherein EC accounts for 25% of the total mass of the organic solvent, and EMC and DMC account for 80% of the total mass of the organic solvent); a blank electrolyte with a concentration of 1.2 mol / L is obtained (wherein the weight percentage content of lithium salt contained in the blank electrolyte is 2 wt%); the weight percentage content of additive 1 (TTP) contained in the lithium ion battery electrolyte is 3 wt%, and the weight percentage content of additive 2 (NST) contained is 0.2 wt%. Others are the same as in Example 1.

[0054] Comparative Example 1

[0055] This comparative example provides a blank electrolyte and a preparation method thereof.

[0056] The difference between this comparative example and Example 1 is:

[0057] A blank electrolyte comprising lithium hexafluorophosphate (LiPF 6 ), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC).

[0058] A method for preparing a blank electrolyte, wherein no additive is added. Other aspects are the same as those in Example 1.

[0059] Comparative Example 2

[0060] This comparative example provides a lithium ion battery electrolyte and a preparation method thereof.

[0061] The difference between this comparative example and Example 1 is:

[0062] A lithium-ion battery electrolyte comprising lithium hexafluorophosphate (LiPF 6 ), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), additive 1 (TTP), the structural formula of the additive 1 (TTP) is shown in formula (3):

[0063]

[0064] A method for preparing a lithium ion battery electrolyte, wherein only additive 1 (TTP, with a structural formula as shown in formula (3)) is added, and additive 2 (NST) is not added. Other aspects are the same as those in Example 1.

[0065] Comparative Example 3

[0066] This comparative example provides a lithium ion battery electrolyte and a preparation method thereof.

[0067] The difference between this comparative example and Example 1 is:

[0068] A lithium-ion battery electrolyte comprising lithium hexafluorophosphate (LiPF 6 ), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), additive 2 (NST), the structural formula of the additive 2 (NST) is shown in formula (4):

[0069]

[0070] A method for preparing a lithium ion battery electrolyte, wherein only additive 2 (NST, with a structural formula as shown in formula (4)) is added, and additive 1 (TTP) is not added. Other aspects are the same as those in Example 1.

[0071]

Performance test and result analysis

[0072]

Physical Characterization

[0073] Lithium-ion battery electrolyte and blank electrolyte were prepared according to the methods in Example 1 and Comparative Example 1, respectively. Graphite was used as the negative electrode material, NCM811 was used as the positive electrode material, and polyethylene (PE) was used as the separator to assemble a graphite / NCM811 full battery. The microscopic morphology of the surface and interior of the positive electrode 811 material after long circulation in the blank electrolyte was characterized by a focused ion beam scanning electron microscope (FIB-SEM, Helios G5 CX, USA). The microscopic morphology of the surface and interior of the positive electrode 811 material after long circulation in the lithium-ion battery electrolyte in Example 1 was characterized by a focused ion beam scanning electron microscope (FIB-SEM, Helios G5 CX, USA). Figure 1 Figure a shows the surface morphology of the positive electrode 811 material after long cycling in blank electrolyte. Figure 1 Figure b is a surface morphology of the positive electrode 811 material after long-term circulation in the lithium-ion battery electrolyte in Example 1. Figure 1 Figure c shows the internal morphology of the positive electrode 811 material after long cycling in blank electrolyte. Figure 1 Figure d is a diagram showing the internal morphology of the positive electrode 811 material after long-term cycling in the lithium-ion battery electrolyte in Example 1.

[0074] Figure 1 Figures a and c in the figure show the morphology of the surface and cross section of the battery electrode without additives, showing more cracks and uneven lithium deposition; Figure 1 Figures b and d show the surface and cross-sectional morphology of the electrode after adding two-component additives (Additive 1 and Additive 2). The surface is smoother, the internal structure is uniform, and the cracks are greatly reduced.

[0075]

Electrochemical characterization

[0076] Test method: Battery assembly: Use graphite as the negative electrode material, NCM811 as the positive electrode material, and polyethylene (PE) as the separator to assemble into a graphite / NCM811 full battery.

[0077] Test conditions: The battery was charged and discharged at a rate of 1C, the voltage range was set to 2.8-4.7 V, and all tests were performed at an ambient temperature of 30°C.

[0078] Test cycle: The battery undergoes 200 charge and discharge cycles.

[0079] Lithium ion battery electrolyte and blank electrolyte were prepared according to the methods in Example 1 and Comparative Examples 1 to 3, and the above electrochemical tests were performed using the corresponding electrolytes. The capacity retention rate comparison of the graphite / NCM811 full battery under 1C 2.8-4.7V and 200 cycles after using different electrolytes is shown in the figure below. Figure 2 shown.

[0080] from Figure 2 From the analysis, it can be seen that the battery with the addition of the two-component additives TTP and NST (red curve, Example 1) has a capacity retention rate of 99.4% after 200 charge and discharge cycles; the battery with the addition of the additive TTP alone (blue curve, Comparative Example 2) has a capacity retention rate of 81.9%; the battery with the addition of the additive NST alone (green curve, Comparative Example 3) has a capacity retention rate of 62.9%; and the capacity retention rate of the battery without any additives (gray curve) is only 58.3%.

[0081] In summary, the synergistic effect of the two-component additives TTP and NST significantly improved the microstructure and macroscopic electrochemical properties of the NCM811 electrode, and improved the cycle stability and capacity retention of the battery. The role of the two-component additives (Additive 1 and Additive 2) in the electrolyte constructs the LiF and Li 3 N positive electrode-electrolyte interface layer and negative electrode-electrolyte interface layer, effectively inhibiting electrolyte decomposition and non-uniform deposition of lithium. 3 The electrode-electrolyte interface layer regulated by N component combination has both high mechanical strength and high flux Li + The migration channel is beneficial to protect the electrode material from the erosion of the electrolyte while promoting rapid and uniform Li deposition, enhancing the crack resistance of the positive electrode 811 material, thereby enhancing the overall performance of the battery.

[0082] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A lithium ion battery electrolyte, characterized in that: The invention comprises a lithium salt, an organic solvent, an additive 1 and an additive 2, wherein the structural formula of the additive 1 is shown in formula (1), and the structural formula of the additive 2 is shown in formula (2): wherein R1 to R8 are independently selected from any one of a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkyleneoxy group having 1 to 10 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 10 carbon atoms, a substituted or unsubstituted alkenyleneoxy group having 2 to 10 carbon atoms, a substituted or unsubstituted epoxyalkylene group having 2 to 10 carbon atoms, a substituted or unsubstituted boroxyalkylene group having 1 to 10 carbon atoms, and a substituted or unsubstituted arylene group having 6 to 10 carbon atoms.

2. A lithium ion battery electrolyte according to claim 1, characterized in that: The lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium difluorooxalatoborate, lithium hexafluoroarsenate and lithium difluorophosphate.

3. A lithium ion battery electrolyte according to claim 1, characterized in that: The organic solvent is any one or more combinations of cyclic carbonate, chain carbonate, and carboxylate co-solvents.

4. A lithium ion battery electrolyte according to claim 1 or 3, characterized in that: The organic solvent is any one or more of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate.

5. The method for preparing a lithium ion battery electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: In a glove box, a lithium salt is added to an organic solvent under stirring and completely dissolved to obtain a blank electrolyte; then, additive 1 is added to the blank electrolyte, and after it is fully dissolved, additive 2 is added thereto to obtain a lithium-ion battery electrolyte.

6. The method for preparing a lithium ion battery electrolyte according to claim 5, characterized in that: The concentration of the blank electrolyte is 0.8~1.2mol / L.

7. The method for preparing a lithium ion battery electrolyte according to claim 5, characterized in that: The weight percentage content of the additive 1 contained in the lithium-ion battery electrolyte is 0.2-3wt%.

8. The method for preparing a lithium ion battery electrolyte according to claim 5, characterized in that: The weight percentage content of the additive 2 contained in the lithium-ion battery electrolyte is 0.2-3wt%.

9. The method for preparing a lithium ion battery electrolyte according to claim 5, characterized in that: The weight percentage of lithium salt contained in the blank electrolyte is 1~2wt%.

10. The method for preparing a lithium ion battery electrolyte according to claim 5, characterized in that: The organic solvent comprises cyclic carbonate and chain carbonate, wherein the cyclic carbonate accounts for 20-30% of the total mass of the organic solvent, and the chain carbonate accounts for 70-80% of the total mass of the organic solvent.

Citation Information

Patent Citations

  • High-voltage lithium ion battery electrolyte film-forming additive, electrolyte and battery thereof

    CN111900477A

  • KR20190080040A